THE ASSESSMENT OF PROSPECTS OF PORPHYRY-COPPER MINERALIZATION BY GEOLOGICAL-GEOPHYSICAL MODELING (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
In the article an example of forecasting of porphyry-copper mineralization of RA is discussed. Via the geological-geophysical (gravimetric) modeling, the forecasts for the specific mineralization in depth are given. A relationship between the scales of deposits and the values of the local anomalies of the gravitational field is also established.
Keywords: geological structure; porphyry copper mineralization